ASSESSING THE PREVALENCE, CAUSE AND CONSEQUENCES OF CORRUPTION IN DAGMAWI MINILIK SUB-CITY, BAHIR DAR, ETHIOPIA - ENDALSASA BELAY ABITEW (Universitas Muhammadiyah Yogyakarta, 2019)
ABSTRACTThe main purpose of this study was to assess the prevalence, cause and consequences of corruption in Dagawi Minilk Sub City. The study employed descriptive case study with quantitative and qualitative research approaches. The Sub-city’s manager, sectoral directors and employees were the primary sources of data whereas books, references and periodical reports were secondary data sources. Primary data were gathered from 103 employees using questionnaire and from 5 key informants through interview. However, since seven questionnaires were unreturned, the analysis of the questionnaire was made based on 96 respondents. The quantitative data were analyzed using frequency counts and percentages. The results of the study confirmed that employees of the sub-city have perception that different forms of corruption (especially bribery, nepotism and favoritism) are frequently occurring in the sub-city and has various negative consequences. As a result, this study has identified low payment scales, absence of exemplary leadership, lack of effective supervisions, weak implementation of ethical codes of conduct, ineffective institutional accountability and lack of strict and fast punishment as major causes of corruption in the study area. Moreover, embezzlement of public resource, delaying in service deliver, lowering quality of service, reducing revenue of the state, worsening income inequality and undermines the legitimacy of the government were also identified as the major adverse consequences of corruption. Thus, this study recommends that improving institutional accountability, increasing salary, selecting exemplary leaders, and imposing strict and immediate punishments should be there.